Application of FIB-SEM Techniques for the Advanced Characterization of Earth and Planetary Materials. (25th July 2020) - Gu, Lixin; Wang, Nian; Tang, Xu; Changela, H. G.
Abstract : Advanced microanalytical techniques such as high-resolution transmission electron microscopy (HRTEM), atom probe tomography (APT), and synchrotron-based scanning transmission X-ray microscopy (STXM) enable one to characterize the structure and chemical and isotopic compositions of natural materials down towards the atomic scale. Dual focused ion beam-scanning electron microscopy (FIB-SEM) is a powerful tool for site-specific sample preparation and subsequent analysis by TEM, APT, and STXM to the highest energy and spatial resolutions. FIB-SEM also works as a stand-alone technique for three-dimensional (3D) tomography. In this review, we will outline the principles and challenges when using FIB-SEM for the advanced characterization of natural materials in the Earth and Planetary Sciences. More specifically, we aim to highlight the state-of-the-art applications of FIB-SEM using examples including (a) traditional FIB ultrathin sample preparation of small particles in the study of space weathering of lunar soil grains, (b) migration of Pb isotopes in zircons by FIB-based APT, (c) coordinated synchrotron-based STXM characterization of extraterrestrial organic material in carbonaceous chondrite, and finally (d) FIB-based 3D tomography of oil shale pores by slice and view methods. Dual beam FIB-SEM is a powerful analytical platform, the scope of which, for technological development and adaptation, is vast and exciting in the field of Earth and Planetary Sciences. For example, dual beam FIB-SEM will be a vital technique for the characterization of fine-grained asteroid and lunar samples returned to the Earth in the near future.